2020
DOI: 10.3390/w12020516
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Nitrate Removal from Waters with Low Organic Carbon Concentration Using a Bioelectrochemical System—A Pilot-Scale Study

Abstract: Assessments of groundwater aquifers made around the world show that in many cases, nitrate concentrations exceed the safe drinking water threshold. This study assessed how bioelectrochemical systems could be used to enhance nitrate removal from waters with low organic carbon concentrations. A two-chamber microbial electrosynthesis cell (MES) was constructed and operated for 45 days with inoculum that was taken from a municipal wastewater treatment plant. A study showed that MES can be used to enhance nitrate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Bioelectrochemical systems can be considered to be an effective conjugated system to constructed wetlands for the removal of N from polluted water [7][8][9]. In addition, these systems can be very efficient for removal of organic matter in wastewater treatment [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioelectrochemical systems can be considered to be an effective conjugated system to constructed wetlands for the removal of N from polluted water [7][8][9]. In addition, these systems can be very efficient for removal of organic matter in wastewater treatment [10].…”
Section: Introductionmentioning
confidence: 99%
“…No previous studies could be found on functional genes of other N transformation processes such as dissimilatory nitrate reduction to ammonia (DNRA), anaerobic ammonia oxidation (ANAMMOX), and complete ammonia oxidation (COMAMMOX) in MFC-CWs. Likewise, only few studies have considered greenhouse gas fluxes in MFC-CWs [9,[22][23][24]26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of this study was to achieve a long-term stable NO 3 reduction by denitrification in the constructed MESR for treating wastewater with a low electron donor concentration. However, in our previous study (Lust et al, 2020), where a twochamber MESR was used, the NO 3 reduction rate was relatively low, and a lack of electroactive bacteria was thought to be the cause. The use of two-chamber MESR caused the pH to drift and therefore needed constant neutralizing.…”
Section: Introductionmentioning
confidence: 85%
“…( 2)) (di Capua et al, 2016;Pang and Wang, 2021;Szekeres et al, 2002). A description and graphical representation of the process have been published previously, where NO 3 reduction was studied in a two-chamber microbial electrosynthesis reactor (MESR) (Lust et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Contamination of nitrate in water resources has become significant, and it can be from the discharge of industrial wastewater or nitrogen fertilizers used in agriculture. The maximum allowable concentration of nitrates in drinking water has been set up at around 50 mg NO 3 − /L as higher than that, will be toxic to humans [51]. RO has been used to treat borehole waters in rural areas in South Africa, and it was found to be effectively suitable for water denitrification where the nitrate-nitrogen was reduced from 42.5 mg/L to only 0.9 mg/L in the permeate [52].…”
Section: Removal Of Inorganic Compoundmentioning
confidence: 99%